2013
DOI: 10.1144/qjegh2011-063
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of settlement in peat soils

Abstract: Abstract:Laboratory predictions of the compression behaviour of peat are compared with field data through use of a database of laboratory tests from 14 sites and information from full scale field loading at 5 sites. Data presented confirms the complexity of the deposits.Nonetheless from the point of view of normal engineering works, calculations based on laboratory test data are likely to give reasonable predictions of the magnitude of immediate and primary compression.Standard (20 mm thickness) samples may gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Interestingly, Long and Boylan (2013), reporting values of C c and C c /1 + e 0 for peats in three countries including Ireland, have also found that C c relationships with w n exhibit less scatter than the C c /1 + e 0 relationships with w n . (b) The Mesri and Ajlouni (2007) relationship represents the data quite well for w n values in excess of 60% (Figure 4(a)).…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly, Long and Boylan (2013), reporting values of C c and C c /1 + e 0 for peats in three countries including Ireland, have also found that C c relationships with w n exhibit less scatter than the C c /1 + e 0 relationships with w n . (b) The Mesri and Ajlouni (2007) relationship represents the data quite well for w n values in excess of 60% (Figure 4(a)).…”
Section: Resultsmentioning
confidence: 96%
“…However, this gaseous nature of peat is rarely considered within the geotechnical literature. During laboratory tests, peat is often considered as fully saturated or saturated with very high backpressure (Mesri and Ajlouni 2007;Hendry et al 2012;Long and Boylan 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The four peat specimens used in this testing were cut from a Shelby tube. Shelby tube samples have been used to study the drained and undrained compression behavior of peat (Hendry, Sharma, Martin and Barbour 2012;Long and Boylan 2013). These Shelby tube samples were extruded and trimmed into specimens with diameters of were sealed and stored in a moisture-controlled room with a constant temperature of 1.5°C until they were tested.…”
Section: The Pore Pressure Generation With a Change In Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Authors are encouraged to follow established themes and give due recognition of earlier relevant publications in the journal, whether or not these contribute to computed Impact Factors. The breadth of the subject area encapsulated by engineering geology is captured by papers in the journal, with examples as disparate as stiffness of residual dolomite (Jacobsz 2013), soil abrasion for tunnel boring machines (Barzegari et al 2013), desert engineering geology and geomorphology (Fookes et al 2013), settlement in peats (Long & Boylan 2013), landslide monitoring (Gunn et al 2013), the properties of specific deposits (e.g. the engineering geology of chalk; Bowden 2013) and advances in theory and analysis (e.g.…”
mentioning
confidence: 99%